Satisficers Still Get Away with Murder! - Joe Slater (Ergo, An Open Access Journal of Philosophy)
Recently, a few attempts have been made to rehabilitate satisficing consequentialism. One strategy, initially shunned by Tim Mulgan, is to suggest that agents must produce an outcome at least as good as they could at a particular level of effort. The effort-satisficer is able to avoid some of the problem cases usually deemed fatal to the view. Richard Yetter Chappell has proposed a version of effort-satisficing that not only avoids those problem cases, but has some independent plausibility. In this paper, I argue that we should be concerned by verdicts the effort-satisficer delivers that are too permissive. Revising a problem for the traditional outcome-satisficer, I argue that Chappell’s willpower satisficing, and more generally, any effort-satisficer, must implausibly condone murder in many cases. This seems like a serious issue for any attempts at rehabilitating satisficing consequentialism in this way. After presenting my objection, I consider some ways an effort-satisficer might attempt to revise the account to avoid these problems, but argue that none of these can succeed.